Multimodal digital classroom assessments. (July 2020) - Fjørtoft, Henning
Abstract: Despite the widespread adoption of multimodal and digital modes of representation outside school settings, classroom assessment practices rely more on conventional print media and less on digital technologies. Stronger connections between the use of ICT in schools, contextual factors, and theoretical approaches are needed if teachers are to use digital tools effectively in the classroom. This study explores multimodal digital classroom assessments (MDCAs) as a subset of classroom assessments. Combining multimodal perspectives with performance assessment theory, the paper analyzes three examples of MDCAs developed in collaboration with practitioners as part of a formative experiment and discusses their affordances and potential relevance for practice. MDCAs may offer richer repertoires of modalities for students and teachers. However, implementing MDCAs requires continuous attention to validity, literacy demands, and management of the longitudinal nature of certain MDCAs. Therefore, to provide a meaningful picture of student learning, design processes should consider how evidence from MDCAs complements conventional assessment practices. Highlights: This study explores multimodal digital classroom assessments (MDCAs). The paper analyzes three examples of MDCA practices designed by teachers. MDCAs may offer richer repertoires of modalities available for students and teachers. Implementing MDCAs requires attention to validity, literacy demands, and the longitudinal nature of certain MDCAs.